In vitro study of the Nd : YAG laser effect on human dental enamel: Optical and scanning electron microscope analysis - Pelino, JEP; Mello, J. B.; Eduardo, C. P.; Jorge, AOC (Mary Ann Liebert, Inc., 1999)
Objective: the Nd:YAG laser irradiation of dental enamel was evaluated in enamel demineralization experiments in a Streptococcus mutans culture media. Summary Background Data: Previous studies had shown that a continuous wave Nd:YAG laser at an energy of approximately 67 mJ may induce an increased acid resistance in human dental enamel when exposed to severe demineralization conditions. Methods: Enamel windows of 3 x 4 cm in the buccal surface were irradiated with a continuous wave Nd:YAG laser at a wavelength of 1,064 Ecm using energy densities of from 83.75 to 187.50 J/cm(2), Enamel windows of 3 x 4 cm on the lingual surface served as control (without the laser irradiation). The enamel windows were then exposed to a Streptococcus mutans culture media at a temperature of 37 degrees C for 15 and 21 days. The laser effects and demineralization were examined both by optical microscopy and scanning electron microscopy (SEM), Results: A comparison between the lased and the unlased windows of enamel showed fusion and recrystalization of the enamel and increased acid-resistance in all groups irradiated with the Nd:YAG laser, on the other hand, the 3 x 4 delimited enamel surfaces from the control group (not irradiated with the Nd:YAG laser) showed 100% deminerization, Conclusions: These findings are consistent with the finding that laser irradiation of dental results in significant reduction of the effective solubility of enamel mineral.